Usher's Syndrome Type II: A Comparative Study of Genetic Mutations and Vestibular System Evaluation. (27th June 2017) - Magliulo, Giuseppe; Iannella, Giannicola; Gagliardi, Silvia; Iozzo, Nicola; Plateroti, Rocco; Mariottini, Alessandro; Torricelli, Francesca
Abstract : Objective: Usher's syndrome type II (USH2) is characterized by moderate to profound congenital hearing loss, later onset of retinitis pigmentosa, and normal vestibular function. Recently, a study investigating the vestibular function of USH2 patients demonstrated a pathologic response to vestibular tests. In this cross‐sectional study we performed vestibular tests of a group patients with genetic diagnosis of USH2 syndrome to demonstrate if vestibular damage is present in USH2 patients. Study Design: Cross‐sectional study. Setting: Tertiary referral center. Subjects and Methods: Mutated genes of 7 patients with a clinical diagnosis of USH2 were evaluated. Vestibular function was investigated by audiometry, Fitzgerald‐Hallpike caloric vestibular testing, cervical vestibular evoked myogenic potentials (C‐VEMPs), ocular vestibular evoked myogenic potentials (O‐VEMPs), and video head impulse test (v‐HIT). Results: Genetic tests confirmed the USH2 diagnosis in 5 of 7 patients examined, with 1 patient reporting a unique mutation on genetic tests. Four (80%) of the 5 patients with a genetic diagnosis of USH2 showed pathological O‐VEMPs. Two patients (40%) reported bilateral absent or abnormal values of C‐VEMPs. The superior semicircular canal presented a significant deficit in 2 (40%) patients. The same 2 cases showed a pathologic response of the v‐HIT of the horizontal semicircular canal. Finally, the posterior semicircular canal presented a significant deficit in 4 (40.0%) patients. Conclusion: A vestibular evaluation with vestibular evoked myogenic potentials and v‐HIT seems to identify latent damage to the vestibular receptors of USH2 patients.